Dental health status of children with diabetes in Riyadh, Saudi Arabia - Yousef H. Al-Dlaigan; Rasha A. Al-Dabaan (Saudi Dental Journal)
Objective: The impact of diabetes on oral diseases remains debatable. We aimed to determine the prevalence of dental caries, gingival health status and knowledge, and oral hygiene level and practice in children with type 1 diabetes mellitus in Riyadh, Saudi Arabia. Methods: The teeth of Sixty children with diabetes (33 males and 27 females; age 11.3 ± 2.2 [7–14] years) were examined for dental caries following the modified World Health Organization criteria. Data on age, sex, medical history, gingival health status and knowledge, and oral hygiene level and practice were collected from parents. Results: In this study, 53 % of the children had dental caries with decayed, missing, and filled primary and permanent teeth scores of 5.6 ± 3.8 and 3.6 ± 3.2, respectively, with similar scores for male and female children. Children with and without caries had similar oral hygiene practices and oral health knowledge but differed in the rates of good or fair oral hygiene status (89.2 vs. 56.6 %; P = 0.024) and normal gingival health status or mild gingivitis (96.5 vs. 81.3 %; P = 0.010). Conclusions: We found that the oral hygiene status and rate of gingivitis differed in children with type 1 diabetes mellitus with or without dental caries.